Models of vertical swimming abilities in elite female senior water polo players - Dopsaj, M. (Biomechanics and Medicine in Swimming XI, 2010)
(VSA) in elite female senior water polo (WP) players with regard to all three energetic systems of swim effort. The study included 30 female WP players, members of the Serbian senior national team. On the basis of raw data obtained through testing (four different test loads: 10, 12, 13.5 and 16 kg) the function of Power-Time equation was calculated for each subject applying the general equation y=a·bx. All data are presented in absolute terms as Absolute Vertical Swim Abilities Model (ABSvswim), in relative terms as Relative Vertical Swim Abilities Model (RELvswim), and in terms of reached biological capacity as Capacity Vertical Swim Abilities Model (CAPvswim). The raw data were used to define the following models of VSA in female WP players: ABSvswim, y = 30.4868x-0.2087, RELvswim, y = 47.8754x-0.2127, CAPvswim, y= 91.9195x-0.1846, respectively.